2018
DOI: 10.2147/ott.s161200
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation and DNA methylation of ECRG4 in gastric cancer

Abstract: BackgroundEsophageal cancer-related gene 4 (ECRG4) is a novel candidate tumor suppressor gene. Our study investigated the expression and function of ECRG4 in gastric cancer and highlighted the role of DNA hypermethylation at the promoter in silencing the ECRG4 expression.MethodsThe GSE63089 data set was obtained from the Gene Expression Omnibus and analyzed for differentially expressed genes. Carcinoma and para-carcinoma tissues of 102 patients with gastric cancer were collected from January 2010 to July 2011.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…A study has reported that ECRG4 is downregulated and acts as a tumor suppressor gene in most types of cancers (Qin and Zhang, 2019). Several studies have shown that the ECRG4 promoter is frequently hypermethylated in patients with breast cancer, gastric cancer, and nasopharyngeal carcinoma, resulting in the downregulation of ECRG4 (You et al, 2015;Deng et al, 2018;Tang et al, 2019). Consistent with a previous study that reported that ECRG4 is hypermethylated in BCa cells (Rose et al, 2020), our results further demonstrated that ECRG4 is significantly downregulated in BCa tissues and cell lines.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A study has reported that ECRG4 is downregulated and acts as a tumor suppressor gene in most types of cancers (Qin and Zhang, 2019). Several studies have shown that the ECRG4 promoter is frequently hypermethylated in patients with breast cancer, gastric cancer, and nasopharyngeal carcinoma, resulting in the downregulation of ECRG4 (You et al, 2015;Deng et al, 2018;Tang et al, 2019). Consistent with a previous study that reported that ECRG4 is hypermethylated in BCa cells (Rose et al, 2020), our results further demonstrated that ECRG4 is significantly downregulated in BCa tissues and cell lines.…”
Section: Discussionsupporting
confidence: 91%
“…Esophageal cancer-related gene-4 (ECRG4 or C2orf40) has been characterized as a tumor suppressor gene in several types of cancers, such as colorectal cancer ( Gotze et al, 2009 ; Cai et al, 2016 ), esophageal squamous cell carcinoma (ESCC; Mori et al, 2007 ; Li et al, 2011 ; Wen and Hu, 2015 ), breast cancer ( Sabatier et al, 2011 ; Lu et al, 2013 ; You et al, 2016 ; Tang et al, 2019 ), renal cell carcinoma ( Luo et al, 2016 ), gastric cancer ( Deng et al, 2018 ), and nasopharyngeal carcinoma ( Chen J.Y. et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found a CpG island was located in the prmoter region of UNC5A, implying the possibility of epigenetic regulation of UNC5A. The expression of epigenetically silenced gene could be recovered by demethylation agent 5-Aza ( Deng et al, 2018 , Karakoula et al, 2014 , Yamamura et al, 2013 ). Thus, we measured UNC5A expression in NSCLC cells cultured in the presence of 5-Aza.…”
Section: Discussionmentioning
confidence: 80%
“…C2orf40 encodes a protein called esophageal cancer-related gene-4 (ECRG4), which is down-regulated by hypermethylation of its promoter in diverse types of tumors, including hepatocellular carcinoma [33], gastric cancer [34],breast cancer [35].…”
Section: Discussionmentioning
confidence: 99%